A Modern Approach to Analyzing the Flowing Pressures of a Two-Phase CBM and Water Column in Producing Wellbores - Xinfu Liu; Chunhua Liu; Jianjun Wu (Geofluids)
A modern methodology is presented for the system analysis of flowing pressures in order to forecast the dynamic behavior and solve the forthcoming problems that emerge in two-phase coalbed methane (CBM) wellbores. The proposed methodology involves a numerical integration technique to calculate flowing pressures and pressure drops of CBM and water flow from the bottom hole to the well head. The methodology is validated against full-scale measured data in coalfields. The relationships developed match CBM reservoir behavior and wellbore conditions along the annulus with an overall accuracy of 1.13%. The computation of flowing pressures involves a liquid holdup and kinetic energy term with flow rate increments, a compressibility factor with depth increments, and a friction factor with Reynolds number. The flowing pressures of a two-phase column fully reflect the dynamic flowing performance due to the combined action of the water level, CBM, and water flow rates. The effect of CBM and water column pressures is more obvious than that of CBM column pressures. The pressure ratios of CBM and the water column to the bottom hole decline rapidly with the increase of the dynamic water level. CBM and water flow rates can be improved with increases in CBM and water column pressure for two-phase producing wellbores. The decrease of flowing pressures and increased increment of the pressure drop for the two-phase column are beneficial to CBM desorption and result in the increased CBM and water production. It will control the falling speed of the dynamic water level above CBM and the water column and enhance CBM reservoir productivity. The increases of CBM and water column pressure from 34.6 kPa to 922 kPa and the decreases of pressure in the bottom hole from 2.252 MPa to 1.328 MPa lead to the increases of the CBM flow rate from 3327 m3/d to 6721 m3/d.